2020
DOI: 10.1590/1983-21252020v33n321rc
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Post-Harvest Fruit Quality of West Indian Cherry Under Saline Water Irrigation and Potassium Fertilization

Abstract: The study was conducted to evaluate the growth and physicochemical quality of West Indian cherry cv. BRS 366-Jaburu, as a function of saline water irrigation and potassium fertilization. The research was conducted under greenhouse conditions in Campina Grande-PB. The experimental design was randomized blocks in a 2 x 4 factorial arrangement, which consisted of two levels of irrigation water electrical conductivity - ECw (0.8 and 3.8 dS m-1) and four levels of potassium of 50, 75, 100 and 125% of the recommenda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Considering the importance of using saline water for the expansion of irrigated agriculture and guarantee of food production, it is necessary to take action on strategies that minimize the deleterious effects of this abiotic stress, enabling safe agricultural production in the semi-arid region and promoting socioeconomic and environmental development (LIMA et al, 2020). In this context, research has been conducted using salicylic acid to mitigate the effects of salt stress on common bean (ARAÚJO et al, 2018), watermelon (NÓBREGA et al, 2020), basil (SILVA et al, 2019), soursop (SILVA et al, 2020b) and West Indian cherry (DANTAS et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the importance of using saline water for the expansion of irrigated agriculture and guarantee of food production, it is necessary to take action on strategies that minimize the deleterious effects of this abiotic stress, enabling safe agricultural production in the semi-arid region and promoting socioeconomic and environmental development (LIMA et al, 2020). In this context, research has been conducted using salicylic acid to mitigate the effects of salt stress on common bean (ARAÚJO et al, 2018), watermelon (NÓBREGA et al, 2020), basil (SILVA et al, 2019), soursop (SILVA et al, 2020b) and West Indian cherry (DANTAS et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of SD in plants was also observed by Xavier et al (2022), in a ). The inhibition of plant growth is related to changes in soil water potential caused by excess salts, which restrict water absorption, decreasing turgor pressure and plant cell activity by inhibiting cell expansion and elongation (Lima et al, 2020a;Lima et al, 2020b). H 2 O 2 concentrations showed a quadratic effect on the SD of soursop cv.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the post-harvest quality of fruits in plants grown under salt stress conditions occur due to the action of the osmotic effect in the soil solution, reducing the flow of free energy of water and inhibiting the absorption of water and nutrients by plants, as well as photosynthetic capacity (Lima et al, 2020). The results found in the present study differ from those reported by Lima et al (2020), who evaluated the West Indian cherry crop under salt stress conditions with levels of 0.8 and 3.8 dS m -1 and found that the highest anthocyanin content in fruit pulp was found at the highest level of water salinity.…”
Section: Resultsmentioning
confidence: 99%
“…The highest level of ECw was established based on studies conducted by Bezerra et al (2019) with guava cv. Paluma, while salicylic acid (SA) concentrations used were based on a study conducted by Silva et al (2020) with soursop (Annona muricata L.) crop.…”
Section: Methodsmentioning
confidence: 99%